Edukasi Daur Ulang Sampah Sebagai Upaya Pencegahan Terjadinya Pencemaran Lingkungan Akibat Sampah Plastik di Sdi Wolotopo - Nining Sariyah; Yuliani Sepe Wangge; Maria Irmagardis Pao; Virgilius Bate Lina; Anselmus Mema; Berty Sadipun (Institut Teknologi dan Bisnis Semarang, 2023)
Garbage is goods or objects that are thrown away because they are no longer used. Indiscriminate disposal of waste will cause various negative impacts on humans, other living things and for the environment itself. Plastic waste is waste that causes soil and water pollution. Plastic waste cannot be simply thrown into the ground, because it is difficult for microorganisms to decompose in the soil because of its long carbon chain. One way to deal with plastic waste is to carry out the waste recycling process. The purpose of this activity is to provide knowledge and increase the skills of SDI Wolotopo students on how to process plastic waste to reduce air pollution and environmental pollution. The methods used in this community service activity are situation analysis methods, social approaches, problem identification, determining work goals, implementing activities and evaluating activity results. This activity was carried out well. students are able to increase their knowledge and creativity in managing plastic waste into useful items.